Faktor Internal dan Eksternal yang Memengaruhi Status Putus Sekolah di Provinsi DKI Jakarta Tahun 2021 - Purba, Mikael; Ekaria, Ekaria (Politeknik Statistika STIS, 2023)
Dropping out of school is a complex and varied problem, and is often seen as a serious social problem. DKI Jakarta is one of the provinces with a school dropout rate above the national level. Since 2012, the Provincial Government of DKI Jakarta has launched 12 years of compulsory education. In fact, the condition of dropping out of school in DKI Jakarta is still far from reaching the target to be achieved. This study aims to obtain an overview of the variables in internal and external factors in dropout status in children aged 7-18 years in DKI Jakarta Province in 2021 and find out the variables that influence them. The data used is raw data from the results of the 2021 National Socioeconomic Survey. The analysis method uses binary rare event logistic regression with the estimation of the Firth's Penalized Maximum Likelihood Estimator (PMLE) parameter. Based on the research results, the dropout rate in DKI Jakarta Province in 2021 at the SD/equivalent, junior high/equivalent, and high school/equivalent levels is still above the national rate. Variables that affect the status of dropping out of school in DKI Jakarta Province, from internal factors, consist of variables of child employment status, child's relationship with the head of household, and status of managing the household, as well as from external factors, consisting of variables of poverty status and education level of the head of household. The dropout status of children in DKI Jakarta Province is most at risk for working children.